2020
DOI: 10.3390/app10249128
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of a Serious Game for Working Memory Enhancement

Abstract: The amount of information which can be stored in the human brain is limited and dependent on memory capacity. Over the last few years there has been a trend in training cognitive skills, not only to prevent cognitive decline, which is inevitable as a person grows older, but also to increase or at least preserve mental abilities that will allow a person to function at a higher cognitive level. Memory is one of those key aspects among cognitive skills that has a significant role in a person’s mental performance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Nowadays, because of the advance of science and technology in video games and smartphones, serious games have become more popular, especially in training and educational areas. They can be used for cognitive training, and previous studies have shown that there are different kinds of cognitive function training that employ serious games [67][68][69][70].…”
Section: Serious Gamementioning
confidence: 99%
“…Nowadays, because of the advance of science and technology in video games and smartphones, serious games have become more popular, especially in training and educational areas. They can be used for cognitive training, and previous studies have shown that there are different kinds of cognitive function training that employ serious games [67][68][69][70].…”
Section: Serious Gamementioning
confidence: 99%
“…In the first case, the user is required to handle a device and apply a physical pressure to a surface to trigger events. Whereas, in the second case, [2], [4], [5], [7], [10], [11], [18], [22], [24], [25], [28], [30], [34], [45], [51], [53], [60]- [121] 79 Mobile devices [13], [16], [19], [26], [31], [36], [37], [39], [41], [43], [44], [59],…”
Section: Interaction Technologiesmentioning
confidence: 99%
“…As participants could suffer from visual and hearing problems or have troubles with atten- tion, visual scenes have to be as simple as possible and search space should be reduced. During gameplay, simple and immediate data as a countdown timer, the number of remained chances to guess an answer, the current score or achieved goals are often shown to incentive the subject to answer as quickly and accurately as possible [3], [14], [17], [19], [20], [22], [24], [26], [28]- [31], [33], [38]- [41], [44], [49], [50], [52], [53], [71], [72], [79], [83], [96], [97], [99], [100], [106], [109], [115], [120], [124], [125], [130]- [132], [137], [138], [142], [150], [161], [164], [179], [191], [209], [211], [212], [231],…”
Section: Interaction Technologiesmentioning
confidence: 99%
See 2 more Smart Citations